Cardiac Sympathetic Dominance and Systemic Inflammation in COPD. (3rd September 2015) - Chhabra, Sunil K.; Gupta, Mansi; Ramaswamy, Swapna; Dash, Devi Jyoti; Bansal, Vishal; Deepak, K. K.
Abstract: Cardiac autonomic dysfunction is an independent determinant of adverse outcomes in many diseases. The available literature on the relative changes in sympathetic and parasympathetic components in chronic obstructive pulmonary disease (COPD) is equivocal, the clinical and physiological correlates are poorly defined and association with markers of systemic inflammation has not been explored. As both autonomic dysfunction and systemic inflammation may contribute to cardiovascular morbidity in COPD, we hypothesized that these may be associated. Sixty three stable patients of COPD and 36 controls underwent spirometry, estimation of diffusion capacity, six-minute walk test and measurements of serum interleukin-6 (IL-6) and high-sensitivity C-Reactive protein. Cardiac autonomic activity was evaluated by standard five-minute heart rate variability (HRV) recordings to obtain time- and frequency-domain indices and the averaged heart rate. We observed that HRV indices of overall autonomic modulation, the standard deviation of time intervals between consecutive normal beats (SDNN) and total power, were greater in patients with higher levels of indices of both parasympathetic and sympathetic activity. The heart rate was significantly higher in patients indicating an overall sympathetic dominance and was inversely correlated with diffusion capacity. Serum IL-6 was inversely correlated with pNN50, an index of parasympathetic activity, and positively with LF/HF ratio, a measure of sympathetic: parasympathetic balance. None of the HRV indices was significantly correlated with physiological measures of severity. It was concluded that patients with COPD have increased cardiac autonomic modulation with sympathetic dominance. This is associated with decreased lung diffusion capacity and systemic inflammation.